The Effectiveness of Da'wah Promotion on Television: A Case Study of Damai Indonesiaku TV One in the Sale of Islamic Products - Rhohis Kurniawan; Zen, Muhamad; Fatmawati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The purpose of this study is to analyze the impact of da'wah promotion in television media on TV One “Damai Indonesiaku” program, on consumer purchasing decisions and increasing sales of Islamic products. This research uses a qualitative approach to explore the meaning, perceptions, and experiences of the figures involved in da'wah promotion and their influence on the sale of Islamic products. This research uses a case study method approach, because this research aims to get a comprehensive picture of the effectiveness of da'wah promotion carried out by “Damai Indonesiaku” TV One. Case studies allow in-depth analysis of the communication process, the preparation of da'wah content, and their impact on the sale of Islamic products. Analysis results from previous research on Islamic product manufacturers showed a positive response to the “Damai Indonesiaku” program. Most of them felt that the program provided great benefits in introducing their products to the wider community. Consumers who watched this program stated that the “Damai Indonesiaku” program broadcast on TV One made it easier for them to choose quality, up-to-date products, in accordance with Islamic teachings. Sales data shows a significant increase in products promoted through my “Damai Indonesiaku” program. This program has proven to be effective in increasing consumer awareness about the importance of choosing halal products and in accordance with Islamic principles.